2021
DOI: 10.35848/1347-4065/abee05
|View full text |Cite
|
Sign up to set email alerts
|

Soft X-ray absorption and emission spectra of nanographene prepared from pentacene with hot mesh deposition and soft X-ray irradiation

Abstract: The molecular orientation and partial density of states were evaluated using NewSUBARU by soft X-ray absorption spectroscopy (XAS) and soft X-ray emission spectroscopy measurements. The degree of molecular alignment was degraded by increasing mesh temperature in hot mesh deposition (HMD), in other words, was changed from pentacene (Pn) to 6,13-dihydropentacene (DHP). At a mesh temperature of 1450 °C, the different XAS was obtained due to the mixing effect of Pn and DHP, and presence of Pn oligomer. The HMD car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 68 publications
(92 reference statements)
0
3
0
Order By: Relevance
“…However, acid treatment shows a pronounced effectthe spectral feature intensifies to such an extent that the π* and σ* become nearly indiscernible and it expands across a broad energy range of about 3 eV (286.7–289.6 eV). The carbon K edge NEXAFS of the acid-treated sample highly resembles that of a 6, 13-dihydropentacene (DHP) film prepared via hot mesh deposition as documented in . In , a strong feature at 288.4 eV was attributed to the COOH group, a product of DHP oxidation in air, and a shoulder at 287.5 eV was assigned as aliphatic chain resulting from DHP hydrogenation.…”
Section: Resultsmentioning
confidence: 75%
See 1 more Smart Citation
“…However, acid treatment shows a pronounced effectthe spectral feature intensifies to such an extent that the π* and σ* become nearly indiscernible and it expands across a broad energy range of about 3 eV (286.7–289.6 eV). The carbon K edge NEXAFS of the acid-treated sample highly resembles that of a 6, 13-dihydropentacene (DHP) film prepared via hot mesh deposition as documented in . In , a strong feature at 288.4 eV was attributed to the COOH group, a product of DHP oxidation in air, and a shoulder at 287.5 eV was assigned as aliphatic chain resulting from DHP hydrogenation.…”
Section: Resultsmentioning
confidence: 75%
“…The carbon K edge NEXAFS of the acid-treated sample highly resembles that of a 6, 13-dihydropentacene (DHP) film prepared via hot mesh deposition as documented in . In , a strong feature at 288.4 eV was attributed to the COOH group, a product of DHP oxidation in air, and a shoulder at 287.5 eV was assigned as aliphatic chain resulting from DHP hydrogenation. For the acid-treated electrode investigated in the current work, the sp 2 -bonded COOH is still the most probable functionality given the characteristic peak position at 288.3 eV, but considering that the spectral features of all relevant functional groups presented in untreated carbon electrodes, i.e., sp 2 -bonded CHO, CH 3 , may all overlap with the π* resonance, it is inconclusive to rationalize which functional group dominates the edge functionality of acid-treated carbon electrodes.…”
Section: Resultsmentioning
confidence: 75%
“…Heya et al (Heya et al, 2020, Heya et al, 2021) irradiated pentacene to obtain nanographene. Evlyukhin et al (Evlyukhin et al, 2018) reported the combination of high-pressure and X-ray exposure for the synthesis of oxalates.…”
Section: Othersmentioning
confidence: 99%